2017
DOI: 10.1272/jnms.84.237
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia Procedure for Congenital Insensitivity to Pain in a Child with Anhidrosis Syndrome: A Rare Case

Abstract: Congenital insensitivity to pain with anhidrosis (CIPA) syndrome is a neuropathy characterized by insensitivity to pain, impaired thermoregulation, anhidrosis, and mental retardation. A 9-year old boy with CIPA syndrome, underwent 2 operations for a calcaneal ulcer. During the first operation standard monitorization was performed. In the second operation, Bispectral Index (BIS) monitoring was added and temperature was monitored with an esophageal probe. In the first operation, in which anesthesia induction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to current literature, some patients can be operated on while sedated 12 ; however, it is believed that while these patients are insensitive to pain, paradoxically, they may have hyperalgesia. Some CIPA cases have reported perioperative somatotropic reactions caused by increasing surgical stimulation and postoperative pain complaints 13,14 . Therefore, it has been proposed that opioid analgesics should be used in surgical treatment for this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to current literature, some patients can be operated on while sedated 12 ; however, it is believed that while these patients are insensitive to pain, paradoxically, they may have hyperalgesia. Some CIPA cases have reported perioperative somatotropic reactions caused by increasing surgical stimulation and postoperative pain complaints 13,14 . Therefore, it has been proposed that opioid analgesics should be used in surgical treatment for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Some CIPA cases have reported perioperative somatotropic reactions caused by increasing surgical stimulation and postoperative pain complaints. 13,14 Therefore, it has been proposed that opioid analgesics should be used in surgical treatment for this patient population. In addition, it has been found that heart rate, blood pressure, and body temperature all rise significantly when patients are intubated without opioid analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of anesthesia management is also limited due to the rare occurrence of the syndrome. Although general anesthesia was preferred in most of the studies, [12] there were case presentations which only sedation was performed. [13] Even though general anesthesia provides surgical comfort for surgeon, it increases the susceptibility to anesthesia complications due to hemodynamic instability and hyperthermia because of autonomic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This gene is responsible for nerve growth factor (NGF) effects, and it helps in the development of the nociceptive, sensory and sympathetic neurons during the embryological period. 2 Symptoms of this disease begins in infancy. Common clinical presentations include anhidrosis, insensitivity to noxious stimuli leading to self-mutilating behavior, and intellectual disability.…”
Section: Introductionmentioning
confidence: 99%